Da’wah Communication of Pondok Modern Darussalam Gontor Through Gontor TV’s Youtube Channel - Muhammad Saufi Afliga; Nur Aini Shofiya Asy’ari (Universitas Darussalam Gontor, 2018)
AbstractThe era of the rapid development of internet technology, makes people use new media to access all their needs. With the existence of new media, it emerges da'wah communication through new media. Da’wah Communication uses new media is as a new forum for Ulama, Community Organization, and educational institution in spreading syiar of Islam. Pondok Modern Darussalam Gontor (PMDG) as an educational institution based on pesantren using new media (youtube) as communication tool of PMDG preaching to society. Gontor TV’s Youtube Channel is one form of PMDG preaching communication in spreading the teachings of Islam, Education and Gontor Values to the community in Indonesia and even abroad. The purpose of this study is to find out how the da'wah communication done by PMDG through Gontor TV youtube channel and the da'wah messages delivered by PMDG through youtube channel of Gontor TV. This type of research is qualitative descriptive research. In collecting the data, the researcher used interview method, observation, and documentation. Based on the results of the analysis of research, some conclusions can be drawn as follows:1). In implementing da'wah communication, PMDG utilizes Gontor's youtube channel containing video content which is published on its channel in the form of: Islamic music, short movie, lecture, qiroahatul-qur'an and prayer, and variations of the program. 2). Da’wah messages delivered through the channel PMDG youtube Gontor consists of: a) Akhlaq message, b) Sharia message, c) Morals messages, which are packaged in some form of impressions. It is hoped that this research can contribute to the development of Gontor TV and donation to the preaching communication of da'wah through new media.Keywords: Communication Da’wah, Gontor,Youtube.